Say cheese and die-- again! - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1996)
Bad things happen when Greg determines to convince his English teacher of the powers of the evil camera.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
G2
Keywords: Horror tales; Horror fiction